Tanggung Jawab Hukum Terhadap Hilangnya Nyawa Orang Di Lubang Tambang Batu Bara Ditinjau Dari Perspektif Hukum Pidana (Studi Kasus PT. Cahaya Energi Mandiri (CEM), kelurahan Sambutan Kecamatan Samarinda Ilir) - Rustiana Rustiana (Yuriska: Jurnal Ilmiah Hukum, 2019)
The use of natural resources in coal mining has many positive and negative impacts. The positive impact is increasing economic and social development both for the community in terms of employment and the government of the Province of East Kalimantan and the Regency of the City of the Producer in terms of Regional Original Revenue (ROR). Negative impacts include the destruction of forests in the area around the mine, contamination of the sea, disease outbreaks for people who live in the area around the mine, even the real negative impact on mining that makes the loss of one's life due to ex-mining holes, legally the case of responsibility for loss of life the person in the coal mine pit is not one person responsible, but there are some responsible parties.The object of research is PT. Cahaya Energi Mandiri, and the Government and the police related to the loss of life of people in mining pits or Mining Business License (IUP) of PT. Cahaya Energi Mandiri. So the purpose of this first thesis is to know and analyze the Legal Responsibility to the Loss of People Life at the Coal Mine Hole Judging from the Perspective of Criminal Law, the second to know and analyze the elements of criminal acts associated with the field of coal mining.The research method used is the normative-empirical legal research method that is merging between the approach of normative law with the addition of various empirical element.From the results of the research can be seen that the loss of life of the pit hole people have met the elements in the provisions of criminal law, because the loss of the lives of people perforated mine has met the elements in Article 359 KUHP and article 112 of Law Number 32 the Year 2009 on Protection and Environmental Management. While the criminal law responsibility can be imposed on the holders of IUP and the Government as the party responsible for environmental monitoring by punishment in the form of imprisonment or restitution or compensation for the victim or his family by the perpetrator.